Indicadores de produção científica na concepção teórica da indexação: uma análise bibliométrica do periódico The Indexer - Dal'Evedove, Roberta Cristina; Dal'Evedove, Paula Regina [UNESP]; Boccato, Vera Regina Casari; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2013)
In the context of university libraries, optimization services, streamlining processes and consistency of processing and organization of informational content are strongly influenced by the indexing policy adopted by the information system. This discussion has proposed to perform a theoretical and methodological research on the subject cataloging in order to contribute to the definition of indexing policy elements in medical university library. To achieve our objective, we applied three instruments: Organizational Culture, Individual Verbal Protocol and Evaluation of Indexing. Considers the importance of developing an indexing policy for improvements in processes and services offered by university libraries, as well as the retrieval.

Se presenta un análisis de los indicadores de citas de artículos publicados en la revista The Indexer entre 2005 hasta 2012. Se procedió al análisis, preparación, almacenamiento, integración y tratamiento bibliométrico de los datos utilizando Excel y Pajek. Los indicadores bibliométricos de producción científica analizados fueron la distribución de artículos científicos y co-autoria por años; la distribución de artículos publicados por sección; la frecuencia de las palabras clave de los artículos identificados; los actores más productivos; análisis de citas y co-citas; la distribución de citas a plazos; las publicaciones más citadas; y la red de co-citas de los autores más citados, identificando el frente de investigación en el enfoque de la revista.
Indicadores de la producción científica en la corriente teórica de la indización: un análisis bibliométrico de la revista The Indexer
Scientific production indicators in the approach of indexing: a bibliometric analysis of the journal The Indexer
Keywords: indexação; comunicação científica; indicadores de comunicação científica; análise de citações